2007
DOI: 10.1177/1081180x06297572
|View full text |Cite
|
Sign up to set email alerts
|

Where Does Issue Ownership Come From? From the Party or from the Media? Issue-party Identifications in Belgium, 1991-2005

Abstract: Although widely used in political science to tackle voting behavior and campaign strategy, the issue-ownership thesis remains untested when it comes to the origins of parties’ identification with specific issues. This article explores where issue ownership comes from and/or how it is maintained. The authors test two possible avenues of issue ownership: the party and the mass media. On one hand, parties’ own external communication may stress specific issues, claiming to be best placed to solve these issues. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 11 publications
4
95
0
6
Order By: Relevance
“…This dynamic part is affected by news coverage of issues and parties. A study on the sources of issue ownership showed that while party programs affect long-term perceptions of issue ownership, media coverage has a more immediate effect on issue ownership perception (Walgrave & De Swert, 2007). In addition, recent experimental research (Bos, Lefevere, Thijssen, & Sheets, 2016;Dahlberg & Martinsson, 2015;Tresch, Lefevere, & Walgrave, 2015;Walgrave et al, 2009) has shown that news messages can affect issue ownership perceptions and vote preferences on the short term.…”
Section: Issue News and Vote Switchingmentioning
confidence: 99%
See 3 more Smart Citations
“…This dynamic part is affected by news coverage of issues and parties. A study on the sources of issue ownership showed that while party programs affect long-term perceptions of issue ownership, media coverage has a more immediate effect on issue ownership perception (Walgrave & De Swert, 2007). In addition, recent experimental research (Bos, Lefevere, Thijssen, & Sheets, 2016;Dahlberg & Martinsson, 2015;Tresch, Lefevere, & Walgrave, 2015;Walgrave et al, 2009) has shown that news messages can affect issue ownership perceptions and vote preferences on the short term.…”
Section: Issue News and Vote Switchingmentioning
confidence: 99%
“…Theoretically, we expect issue news to be related to electoral volatility based on recent research showing that issue ownership also has a volatile component (Walgrave & De Swert, 2007;Walgrave, Lefevere, & Nuytemans, 2009;Walgrave, Lefevere, & Tresch, 2014). The stable component comes from parties' distinctive constituencies (Stubager & Slothuus, 2012).…”
Section: Issue News and Vote Switchingmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of an issue was determined by its salience during the period 1961-2010. We assume that the more an issue was mentioned in the manifestos of the parties of this research, the more electoral (Walgrave and De Swert, 2007) and ideological importance this issue held for a party. Table 4 and 5 show the number of quasi-sentences that were spent on the different categories of the coding scheme.…”
Section: Table 2 and 3 Insert Herementioning
confidence: 99%